Eliminating Excessive Tariffs on Exports of Least Developed Countries - Hoekman, Bernard; Ng, Francis; Olarreaga, Marcelo (Washington, DC: World Bank, 2014)
Although average Organisation for Economic Co-operation and Development (OECD) tariffs on imports from the least developed countries are very low; tariffs above 15 percent have a disproportional effect on their exports. Products subject to tariff peaks tend to be heavily concentrated in agriculture and food products and labor intensive sectors, such as apparel and footwear. Although the least developed countries benefit from preferential access, preferences tend to be smallest for tariff peak products. A major exception is the European Union, so that the recent European initiative to grant full duty free and quota free access for the least developed countries will result in only a small increase in their exports of tariff peak items. However, as preferences are less significant in other major OECD countries, a more general emulation of the European Union initiative would increase the least developed countries total exports of peak products by US dollar 2.5 billion. Although almost half of this increase is at the expense of other developing country exports, this represents less than 0.05 percent of their total exports. This trade diversion can be avoided by reducing tariff peaks to a uniform 5 percent applied on a nondiscriminatory basis. However, such a reform would imply no gains for the least developed countries, suggesting that the globally welfare superior policy of nondiscriminatory elimination of tariff peaks should be complemented by greater direct assistance to poor countries.